Digital ultraviolet and infrared photography - Davies, Adrian, 1953- (Applications in scientific photography., 2018)
"Digital Ultraviolet and Infrared Photography discusses the growing number of applications of ultraviolet and infrared photography. Scientific and technical photographers, such as those engaged in scientific, medical, forensic, and landscape and wildlife photography routinely use ultraviolet and infrared techniques, and these techniques are growing in use in creative photography. This is the first book to address the application and potential for both ultraviolet and infrared photography in both science and art. The author, Adrian Davies, discusses the how-to of ultraviolet and infrared digital recording with a dissection of techniques, camera requirements and camera conversion, a useful appendix of resources and equipment currently available and inspirational image examples throughout. Digital Ultraviolet and Infrared Photography is an essential read for photographers using these tools either professionally or creatively."--Provided by publisher